Modern parliamentary procedure. - Keesey, Ray E. (American Psychological Association, 2018)
This updated and revised edition of Keesey's classic guidebook offers clear rules of order for efficient democratic action in deliberative meetings. streamlines concepts and procedures in the parliamentary process. Brief and concise, this is an easy-to-use teaching tool and at-a-glance guide.